Implementasi Value Stream Mapping untuk Pertimbangan Desain Ulang Tata Letak Fasilitas Produksi - Wedowati, Endang Retno; Puspitasari, Diana; Mrianingsih, Mrianingsih (Universitas Trunojoyo Madura, 2009)
Lay out as apart of production facility problem have to made good design. Good desig11 of lay out production facility will be support good efficiency_ production. Base on that problem, this research aim to redesign lay out (relayout) production faczlzty to make good efficiency production. Relayout production facility can be use Value Stream Mapping Tools. Based on analisis by using Value Stream Mapping Tools can be reduced total cycle timefrom 1022 minutes become 917 minutes, reduce qistance of material handling. Implementatzon of relayout will give good efficinecy productzon.Keyword: relayout, Value Stream Mapping Tools.